Predominant leptospiral serogroups circulating among humans, livestock and wildlife in Katavi-Rukwa ecosystem, Tanzania. - Justine A Assenga; Lucas E Matemba; Shabani K Muller; Ginethon G Mhamphi; Rudovick R Kazwala (Public Library of Science (PLoS), 2015)
BACKGROUND:Leptospirosis is a worldwide zoonotic disease and a serious, under-reported public health problem, particularly in rural areas of Tanzania. In the Katavi-Rukwa ecosystem, humans, livestock and wildlife live in close proximity, which exposes them to the risk of a number of zoonotic infectious diseases, including leptospirosis. METHODOLOGY/PRINCIPAL FINDINGS:A cross-sectional epidemiological study was carried out in the Katavi region, South-west Tanzania, to determine the seroprevalence of Leptospira spp in humans, domestic ruminants and wildlife. Blood samples were collected from humans (n = 267), cattle (n = 1,103), goats (n = 248), buffaloes (n = 38), zebra (n = 2), lions (n = 2), rodents (n = 207) and shrews (n = 11). Decanted sera were tested using the Microscopic Agglutination Test (MAT) for antibodies against six live serogroups belonging to the Leptospira spp, with a cutoff point of ≥ 1:160. The prevalence of leptospiral antibodies was 29.96% in humans, 30.37% in cattle, 8.47% in goats, 28.95% in buffaloes, 20.29% in rodents and 9.09% in shrews. Additionally, one of the two samples in lions was seropositive. A significant difference in the prevalence P<0.05 was observed between cattle and goats. No significant difference in prevalence was observed with respect to age and sex in humans or any of the sampled animal species. The most prevalent serogroups with antibodies of Leptospira spp were Sejroe, Hebdomadis, Grippotyphosa, Icterohaemorrhagie and Australis, which were detected in humans, cattle, goats and buffaloes; Sejroe and Grippotyphosa, which were detected in a lion; Australis, Icterohaemorrhagie and Grippotyphosa, which were detected in rodents; and Australis, which was detected in shrews. Antibodies to serogroup Ballum were detected only in humans. CONCLUSIONS:The results of this study demonstrate that leptospiral antibodies are widely prevalent in humans, livestock and wildlife from the Katavi-Rukwa ecosystem. The disease poses a serious economic and public health threat in the study area. This epidemiological study provides information on circulating serogroups, which will be essential in designing intervention measures to reduce the risk of disease transmission.